Endoscopic En-Bloc Resection of Intra-Muscular Lipoma of the Flexor Digitorum Profundus: A Uniportal Technique - Pui Ying Lam, M.B.Ch.B.; Tun Hing Lui, M.B.B.S. (H.K.), F.R.C.S. (Edin), F.H.K.A.M., F.H.K.C.O.S. (Arthroscopy Techniques, 2023)
Deep-seated lipomas can be intramuscular, intermuscular, and rarely, parosteal lipomas. Intramuscular lipoma can be divided into infiltrative, well-circumscribed, and mixed types. Marginal excision is the treatment of choice for well-circumscribed intramuscular lipoma, and histopathology eliminates diagnosis of well-differentiated liposarcoma. The purpose of this technical note is to describe the details of endoscopic en-bloc resection of intramuscular lipoma of the flexor digitorum profundus. This minimally invasive approach allows en-bloc resection of the lipoma for histopathological study, with minimal risk to the surrounding neurovascular structures.